2003
DOI: 10.1001/archpedi.157.9.882
|View full text |Cite
|
Sign up to set email alerts
|

Television Watching and Soft Drink Consumption

Abstract: Time spent watching television and the number of soft drinks consumed were significantly associated with obesity. Latinos spent more time watching television and consumed more soft drinks than did non-Hispanic white or Asian students. These findings will be beneficial in developing preventive measures for these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(59 citation statements)
references
References 31 publications
6
47
2
1
Order By: Relevance
“…Obesity in humans is associated with lowered daily activity levels (2,3,22,29,49,50,53,68,77). Recent data from our laboratory indicate that postural allocation (i.e., the amount of time sitting or standing throughout the day) dramatically differs between obese and lean individuals (50).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Obesity in humans is associated with lowered daily activity levels (2,3,22,29,49,50,53,68,77). Recent data from our laboratory indicate that postural allocation (i.e., the amount of time sitting or standing throughout the day) dramatically differs between obese and lean individuals (50).…”
Section: Discussionmentioning
confidence: 98%
“…One major contributor to the rise in obesity is the sedentary lifestyle of many individuals, leading to decreased energy expenditure and increased body weight, as well as decreased health quality (3,6,11,22, 29, 30, 34, 36,65,77,82). In fact, energy expended through physical activity is the single most variable component of energy expenditure, and in the majority of individuals, daily physical activity is composed primarily of nonexercise activity (47, 48, 52).…”
mentioning
confidence: 99%
“…Tersine, k›rsal alandaki çocuk-lar aras›nda TV izleme sürelerinin daha uzun oldu¤unu gös-teren yay›nlar da vard›r (54,55). Uzun süre televizyon izleme ile fliflmanl›k ve besin de¤eri düflük, enerji oran› yüksek yiyeceklerin tüketilmesi aras›nda iliflki oldu¤u çok say›da araflt›rmac› taraf›ndan gösterilmifltir (2,5,7,54,56,57). Bir meta-analizde ise uzun süre TV izleme, bilgisayar kullan›m› ve bilgisayar oyunlar› oynama ile fliflmanl›k ve fiziksel etkinlik düzeyinin düflük oluflu aras›nda klinik olarak anlaml› bir iliflki olmad›¤› gösterilmifltir (58).…”
Section: Tart›flmaunclassified
“…A New Zealand tracking study over two decades by Hancox, Milne and Poulton (2004) similarly found that television watching by children and adolescents was associated with overweight, poor fitness, smoking and raised cholesterol in adulthood. Several studies have found that children who watch more television eat more fast food and consume more soft drinks (French et al 2001;Giammattei et al 2003). Anderson et al (1998) show that television watching is associated with childhood obesity.…”
Section: A Focus On the Influence Of Television Advertising And The Imentioning
confidence: 99%